Formal Grammar Instruction: Theoretical Aspects to Contemplate Its Teaching - Cruz Corzo Carolina (Universidad Nacional de Colombia, 2013)
With the rise of new tendencies and methodologies in the English as a foreign language field, formal grammar instruction has become unnecessary during the last few years. Institutions and educators have made serious decisions in order to promote a language production which is fluent and coherent. Thus, grammar instruction has been partially relegated and new trends have occupied its place. However, based on personal teaching practices, I have realized that some learners are producing the foreign language in a fluid, but sometimes inaccurate form. The present reflection is aimed at presenting some insights for educators that may help them consider the possibility of teaching formal grammar as part of the curriculum. Con el crecimiento de nuevas tendencias y metodologías en la enseñanza del inglés, la instrucción formal de la gramática se ha vuelto innecesaria durante las últimas décadas. Instituciones y educadores han tomado serias decisiones con el fin de promover una producción fluida y coherente de la lengua extranjera, lo que ha generado que la enseñanza formal de la gramática sea relegada de manera parcial y nuevas tendencias ocupen su lugar. Con base en mis propias experiencias dentro del aula de clase, he observado que algunos de mis estudiantes se comunican fluidamente en la lengua extranjera, pero en ocasiones, de manera incorrecta. En este artículo de reflexión se presentan algunos elementos teóricos que podrían ayudar a educadores de lengua extranjera a considerar la posibilidad de incluir la enseñanza formal de la gramática en el currículo.